2019
DOI: 10.1186/s10194-019-1002-3
|View full text |Cite
|
Sign up to set email alerts
|

Advanced visual network and cerebellar hyperresponsiveness to trigeminal nociception in migraine with aura

Abstract: BackgroundDespite the growing body of advanced studies investigating the neuronal correlates of pain processing in patients with migraine without aura (MwoA), only few similar studies have been conducted in patients with migraine with aura (MwA). Therefore, we aimed to explore the functional brain response to trigeminal noxious heat stimulation in patients with MwA.MethodsSeventeen patients with MwA and 15 age- and sex-matched healthy controls (HC) underwent whole-brain blood oxygen level–dependent (BOLD) fMRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 36 publications
5
49
0
Order By: Relevance
“…The same group has also recently demonstrated an abnormal response to trigeminal nociceptive stimulation in the lingual gyrus, inferior parietal lobule and cerebellum of MwA patients. This confirms the involvement of areas of higher visual processing in MwA, and possibly shows that functional integration between visual and trigeminal pain networks could represent a key pathophysiological mechanisms underlying migraine with aura (43).…”
Section: Migraine With Aurasupporting
confidence: 76%
“…The same group has also recently demonstrated an abnormal response to trigeminal nociceptive stimulation in the lingual gyrus, inferior parietal lobule and cerebellum of MwA patients. This confirms the involvement of areas of higher visual processing in MwA, and possibly shows that functional integration between visual and trigeminal pain networks could represent a key pathophysiological mechanisms underlying migraine with aura (43).…”
Section: Migraine With Aurasupporting
confidence: 76%
“…Not only the FC of the lingual gyrus in MWA patients has changed, but also the abnormal FC of the lingual gyrus in MwoA patients has been recently discovered. Compared with HC, BOLDresponse of lingual gyrus in MwoA is significantly greater during moderate painful trigeminal nerve thermal stimulation [31]. This finding increases the likelihood of "silent" lingual gyrus hyperactivity in MwoA.…”
Section: Discussionmentioning
confidence: 79%
“…The surface area of the left inferior frontal gyrus increased significantly in the MwoA group compared to that in the normal control group [30]. Compared with HC, the BOLD response of the left inferior frontal gyrus in MwoA was significantly greater when moderately painful trigeminal nerves are thermally stimulated [31]. Some research results showed that spectrum of different colors can selectively regulate the perception of headache intensity.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations